2018
DOI: 10.1038/s41467-018-06780-3
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion modulates specific functional cell types in the mouse visual thalamus

Abstract: The visual system is composed of diverse cell types that encode distinct aspects of the visual scene and may form separate processing channels. Here we present further evidence for that hypothesis whereby functional cell groups in the dorsal lateral geniculate nucleus (dLGN) are differentially modulated during behavior. Using simultaneous multi-electrode recordings in dLGN and primary visual cortex (V1) of behaving mice, we characterized the impact of locomotor activity on response amplitude, variability, corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 48 publications
(75 reference statements)
11
73
0
Order By: Relevance
“…Visual responses in astrocytes were strong during locomotion, but almost absent during periods of stillness. Previous studies in head-fixed mice have demonstrated a clear link between locomotion and elevated arousal [15, 19, 20]. Accordingly, astrocyte responses were not only gated by locomotion but response amplitudes were also correlated with changes in pupil size [14, 16, 17].…”
Section: Resultsmentioning
confidence: 99%
“…Visual responses in astrocytes were strong during locomotion, but almost absent during periods of stillness. Previous studies in head-fixed mice have demonstrated a clear link between locomotion and elevated arousal [15, 19, 20]. Accordingly, astrocyte responses were not only gated by locomotion but response amplitudes were also correlated with changes in pupil size [14, 16, 17].…”
Section: Resultsmentioning
confidence: 99%
“…We then functionally mapped the spatial profile of CT feedback effects by photostimulating the local population of transduced L6CT pyramidal cells during the presentation of full-screen drifting gratings ( Figure 1i ). To avoid potentially confounding, state-dependent response-modulations 41, 42 , we only considered trials in which the animal was quiescent (speed ≤ 0.25 cm/s for ≥ 80% of the trial) for the computation of direction-tuning curves and thus for the evaluation of CT feedback effects. From these curves ( Figure 1i , top), we determined, for each neuron, the relative CT feedback modulation strength as the ratio of responses under L6CT photostimulation to those seen under control conditions (fold change).…”
Section: Resultsmentioning
confidence: 99%
“…As a growing number of studies demonstrate altered levels of neuronal activity according to behavioral-state-dependent changes, in subcortical regions, such as the superior colliculus [43], thalamus [24,44,45], and cerebellum [46][47][48], as well as contextual and experience-dependent changes in higher cortical areas with reciprocally connections to V1 [49], such as the retrosplenial cortex [50][51][52][53][54], the anterior cingulate cortex [35,55], parietal cortex [56], and visual association cortex [41,57,58], it seems likely that these experience-dependent changes in V1 involve modulation of activity in circuits at multiple processing levels. Additionally, neuromodulatory inputs likely play an important role in behavioral-state-dependent plasticity, as cholinergic and noradrenergic influence have already been shown to modulate cortical plasticity, attention, and learning [59,60] in V1, as well as responses to locomotion and behavioral-state changes [22,25,61,62].…”
Section: Discussionmentioning
confidence: 99%